HUBUNGAN KAUSALITAS INVESTASI DENGAN PERTUMBUHAN EKONOMI INDONESIA - Fitri Amalia (Signifikan: Jurnal Ilmu Ekonomi, 2013)
This research aim to know how the relation of causality between investment, in this case governmental investment and investment of private sector with growth of Indonesia. Data applied is data time series during 36 years and is secondary data. There are some variable applied in this research, that is: growth of chartered investment counsel proxy with value GDP, investment of government proxy with disbursement of government, investment of foreign private sector (PMA) and investment of domestic private sector (PMDN). Method applied analyst to the relation of causality is with approach of model Vector Auto Regression (VAR). To test there are no of the relation of causal between variable is applied [by] causality test Granger. Result of testing of Granger indicates that there are three the relation of concurrent. Based on the result, hence chartered gross domestic product (GDP), governmental investment and investment of domestic private sector (PMDN) in significant influences investment of foreign private sector (PMA) and not happened on the contraryDOI: 10.15408/sjie.v2i1.2370